Globalizacja a rozszerzenie Unii Europejskiej na Wschód - Fiedor, Bogusław; Matysiak, Andrzej (Globalization and Integration of World Economy and Eastward Enlargement of European Union, 2005)
The paper stars whit a brief discussion of reasons for making up a homogenous global economic and political deal, with special emphasis being paid to the collapse of communist system, transition from two-pole to one-pole economic and political deal, unprecedented role being played by the United States of North America, and eastward enlargement of the European Union. Following that the authors discuss, in a detailed way, the distinction between globalization and integration, opposing common understanding of those nations in the subject literature. Especially, they point out that there have been some objective reasons for the globalization process (time and space compression and decrease in world-wide transport and communication costs), whereas the integration (at least that one being observed in Europe) is mostly a politically driven or a volitional process. Thereafter, the authors emphasize that the integration contributes both to strengthening market interdependencies and to achieving of strictly defined goals of a given integration community. The main part of the paper is the analysis of regional economic integration being considered by the authors as a "non-phase process". They identify factors which are essential to the transnational coordination of economic activities within an integration community and point out, with respect to those factors, that the economic integration is possible and feasible in a group of pretty homogenous countries merely. In the final part of the paper, the authors deal with factors limiting the international economic integration (as a kind of optimal answer to the globalization process), recognizing three groups of them: political, cultural and economic ones. They also briefly refer to the factors under consideration to the eastward enlargement of the European Union.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1056, s. 35-47